Blood Pressure Fluctuation Pattern Associated with 90‐Day Ischemic Stroke and Transient Ischemic Attack After Total Knee Arthroplasty—A Retrospective Study - Xiao An; Yan Zhang; Zhirui Li; Yuxiang Song; Jiying Chen (Orthopaedic Surgery, 2024)
Objective Blood pressure (BP) fluctuation has been demonstrated to be closely associated with stroke. However, at present, no attention is paid to the BP fluctuation following total knee arthroplasty (TKA). The aim of this study is to investigate what is BP fluctuation patterns in stroke and transient ischemic attack (TIA) patients after primary TKA, compare clinical characteristics among different BP fluctuation patterns and determine whether it could predict the occurrence of a 90‐day stroke. Methods A retrospective study was conducted from February 1, 2011 to February 15, 2021. Stroke or TIA patients within 90 days after TKA were included. Data from a hospitalization management system were analyzed, including demographics, smoking status, comorbidities, medications, surgical variables, and 90‐day stroke, mortality, and readmission rates. BP fluctuation patterns were defined based on the average BP in the first 3 days after TKA. A logistic regression analysis model was used to identify risk factors for 90‐day stroke or TIA following TKA. Results Of the 1687 patients who underwent primary TKA, 4.0% (68/1687) experienced a 90‐day stroke or TIA. A total of 63 patients met the inclusion criteria, with an average age of 67.5 years and 55.6% (35/63) female. The number of stroke or TIA patients in each BP fluctuation pattern (T1–T5) was 6 (9.5%), 5 (7.9%), 4 (6.3%), 13 (20.6%), and 35 (55.6%) respectively. Patients with a T5 pattern tended to be older and had a greater reduction in average systolic blood pressure (SBP) 3 days after surgery compared to other patterns. The T5 pattern was associated with a higher occurrence of stroke and a lower occurrence of TIA. Patients with a T5 pattern also had a longer length of stay within 90 days following TKA. After adjusting for confounding factors, average SBP fluctuation ≥40 mmHg and the T5 pattern of BP fluctuation remained risk factors for 90‐day stroke or TIA after TKA. Conclusion BP fluctuation patterns in the early postoperative period are associated with 90‐day stroke and TIA following primary TKA.